The Role of the Extension Service in Rural/Frontier Disaster - Eighmy, Myron; Hall, Thomas (Australian and International Journal of Rural Education, 2012)
This study was conducted to detennine what the Extension Service's community roles and responses were during flood events and what should be done to better prepare Extension staff for future flooding in rural and frontier counties. A survey was used to determine the extent Extension staff were prepared to respond to citizen requests for services. A joint meeting was held with emergency management organizations to clarify Extension's role in flood-related disasters. The Extension Service has a primary responsibility for providing the public with information and educational materials. Topics were identified for needed disasterrelated educational materials. New materials were developed to fill the gap in previously available resources.